Workplace Violence Against Chinese Frontline Clinicians During the COVID-19 Pandemic and Its Associations With Demographic and Clinical Characteristics and Quality of Life: A Structural Equation Modeling Investigation - Yang, Yuan; Li, Yue; An, Ying; Zhao, Yan-Jie; Zhang, Ling; Cheung, Teris; Hall, Brian J.; Ungvari, Gabor S.; An, Feng-Rong; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: Workplace violence is a major concern for health professionals worldwide. There has been no publication on the epidemiology of workplace violence against frontline clinicians during the COVID-19 pandemic. This study examined the pattern of workplace violence and its association with quality of life (QOL) against frontline clinicians during the outbreak of COVID-19 pandemic in China. Methods: A cross-sectional online study was conducted in China between March 15 and March 20, 2020. Frontline clinicians’ experience with workplace violence was measured with six standardized questions derived from the Workplace Violence Scale, while anxiety, depressive and insomnia symptoms and QOL were measured using the General Anxiety Disorder Questionnaire, the Patient Health Questionnaire, the Insomnia Severity Index and the World Health Organization Quality of Life Questionnaire, respectively. Univariate analyses, multivariable logistic regression analyses, and structural equation modelling (SEM) estimated the prevalence of workplace violence and associations between variables. Results: A total of 15,531 clinicians completed the assessment; 2,878 (18.5%, 95%CI = 17.92%-19.14%) reported workplace violence during the outbreak of the COVID-19 pandemic (verbal violence: 16.1%; physical violence: 6.9%). According to multivariable models, key correlates of workplace violence were male gender, longer work experience, higher education level, smoking, working in the psychiatry or emergency department, working in tertiary hospitals, being involved in direct care of infected patients, having infected family/ friends/ colleagues, and frequently using social communication programs. Workplace violence was negatively associated with working in outpatient clinics. SEM analysis revealed that both violence and emotional disturbances (anxiety, depression, and insomnia) directly affected QOL (standardized direct effect=-0.031, and -0.566, respectively, P<0.05), while emotional disturbances partly mediated the association between work violence and QOL (standardized indirect effect=-0.184, P<0.05). Conclusion: Frontline clinicians were vulnerable to workplace violence during the COVID-19 pandemic. Due to the negative impact of workplace violence on quality of care and clinicians’ QOL, health authorities and policymakers should take effective measures to reduce workplace violence against clinicians.